2003
DOI: 10.1189/jlb0302124
|View full text |Cite
|
Sign up to set email alerts
|

Immature macrophages derived from mouse bone marrow produce large amounts of IL-12p40 after LPS stimulation

Abstract: Production of IL-12 is an important indicator of the macrophage's ability to regulate immune responses. In this study, we investigated the IL-12 production by macrophages in different developmental stages. To this end, macrophages were generated in vitro from precursors stimulated with M-CSF, GM-CSF or IL-3. Density separation yielded populations enriched in different maturation stages. Invariably, only cells banding at the 40-50% Percoll interface produced large amounts of IL-12p40 when stimulated with LPS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…It has been reported that enteric bacteria play essential roles in onset and development of colitis in IL-10 Ϫ/Ϫ mice, similar to human IBDs (15) In the present study, only stimuli from whole bacteria, but not from PAMPs could induce the production of IL-12p70, IL-12 bioactive form consisted of p35-p40 heterodimer, in differentiated M from BM CD11b ϩ cells. In general, TLR ligands such as LPS only induce IL-12p40 subunits, but fail to induce IL-12p70 production from M without IFN-␥ costimulation (36,37). Consistent with this, we also demonstrated that GM-M and M-M produced none or just low levels of IL-12p70 in response to stimulation with various TLR ligands.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that enteric bacteria play essential roles in onset and development of colitis in IL-10 Ϫ/Ϫ mice, similar to human IBDs (15) In the present study, only stimuli from whole bacteria, but not from PAMPs could induce the production of IL-12p70, IL-12 bioactive form consisted of p35-p40 heterodimer, in differentiated M from BM CD11b ϩ cells. In general, TLR ligands such as LPS only induce IL-12p40 subunits, but fail to induce IL-12p70 production from M without IFN-␥ costimulation (36,37). Consistent with this, we also demonstrated that GM-M and M-M produced none or just low levels of IL-12p70 in response to stimulation with various TLR ligands.…”
Section: Discussionsupporting
confidence: 74%
“…The result showed that after 72 hours exposure to 0.5  μ g/mL of rSj16, the nuclear: cytoplasmic ratio of the cells reduced, the nuclear chromatin became condensed and eccentrically placed, the cytoplasmic borders were protruded, and cytoplasmic vacuoles were often present (Figure 3(e)). These morphological features were similar to those described for mature tissue macrophages [15–17]. WEHI-3B JCS cells treated with rGST did not exhibit significant morphological changes (Figure 3(d)).…”
Section: Resultssupporting
confidence: 85%
“…One way to test the effect of stromal cells in BMDM maturation would be to co-culture bone marrow stromal cell line such as M2-10B4 with the myeloid progenitor cells at different ratios and characterizing the final BMDM population. In regards to the relationship between the maturation states of a monocytic cell to their polarization propensity, an earlier study had indicated that immature macrophages secrete more IL-12 [9]. However, a maturation status of a macrophage might be more complex than just defined by cell surface markers or morphology.…”
Section: Resultsmentioning
confidence: 99%